1994
DOI: 10.1071/it9941483
|View full text |Cite
|
Sign up to set email alerts
|

Sandy beach meiofauna of eastern Australia (Southern Queensland and New South Wales). III. Revision of the nematode genus Onyx Cobb, 1891, with a description of three new species (Nematoda : Desmodoridae)

Abstract: Three new species of the desmodoroid genus Onyx are described from ocean beaches of northern New South Wales, Australia: Onyx macramphis, sp, nov., Onyx adenophorus, sp. nov., and Onyx cannoni, sp. nov. The genus Onyx is revised, the status of the type species, O. perfectus Cobb, 1891, is discussed and an annotated list of the species of the genus is presented. The precaudal position of the caudal glands in O. adenophoius prompts a discussion of the significance of the precaudal position of caudal glands in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…nov. is characterized by a relatively smaller body (600–806 μm long) for the genus, amphidial fovea with a single loop, forward in position, gubernaculum slender parallel to spicule and with a hooked dorsal apophysis, 12 S-shaped tubular precloacal supplements fairly evenly spaced. The new species most resembles Onyx macramphis Blome & Riemann, 1994 in the body length (their bodies shorter than 900 μm) but differs from it in amphidial fovea structure (single loop vs spiral with four turns), the number of precloacal supplements (12 vs 14), and anteriorly located vulva (51 vs 55%) in female.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…nov. is characterized by a relatively smaller body (600–806 μm long) for the genus, amphidial fovea with a single loop, forward in position, gubernaculum slender parallel to spicule and with a hooked dorsal apophysis, 12 S-shaped tubular precloacal supplements fairly evenly spaced. The new species most resembles Onyx macramphis Blome & Riemann, 1994 in the body length (their bodies shorter than 900 μm) but differs from it in amphidial fovea structure (single loop vs spiral with four turns), the number of precloacal supplements (12 vs 14), and anteriorly located vulva (51 vs 55%) in female.…”
Section: Methodsmentioning
confidence: 86%
“…This genus differs from other related genera of Family Desmodoridae in the presence of fine cuticle striation, amphidial fovea not surrounded by cuticle striations, buccal cavity with a long-spear-like dorsal tooth, posterior pharyngeal bulb elongated and with a slight constriction in the middle, spicules short and arcuate, precloacal supplements normally S-shaped tubes (Platt & Warwick, 1988). Up to now, 18 species have been recorded in the world (Gerlach & Riemann, 1973; Blome & Riemann, 1994; Hourston & Warwick, 2010; Nasira, Rehmat & Shahina, 2011; Tu et al ., 2011). Out of them, Onyx ferox (Ditlevsen, 1921) Gerlach, 1951 had been described by a single female specimen.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of species grows, especially by the exploration of tropical meiofauna, that leads to increasing complexity in species identification. Coupled with new species description, several reviews of the genus Onyx were suggested ( Blome & Riemann, 1994 ; Nasira, Rehmat & Shahina, 2011 ; Armenteros, Ruiz-Abierno & Decraemer, 2014 ; Huang & Wang, 2015 ). Increase in number of species requires periodical taxonomic revisions with proper adjustment of species composition and construction of improved keys for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of six subfamilies, 35 genera and 318 species (Hodda 2011); but these figures may vary according to the source (e.g., 320 valid marine species in the World Register of Marine Species, accessed February 2014). The six subfamilies currently recognized (Decraemer & Smol 2006) are: Desmodorinae Micoletzky, 1924, Molgolaiminae (Jensen, 1978, Prodesmodorinae Lorenzen, 1981, Pseudonchinae Gerlach & Riemann, 1973, Spiriniinae Gerlach & Murphy, 1965and Stilbonematinae Chitwood, 1936 Several recent taxonomic studies dealt with taxa of the Desmodoridae (e.g., Blome & Riemann 1994;Verschelde et al 1998Verschelde et al , 2006. Five faunistic studies (Gerlach 1950(Gerlach , 1963Wieser 1954;Wieser & Hopper 1967;) described several species of desmodorids and proposed dichotomic keys to species.…”
Section: Introductionmentioning
confidence: 99%